2009
DOI: 10.1111/j.1365-2230.2009.03272.x
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected location of pilonidal sinuses

Abstract: Pilonidal sinuses usually occur in the sacrococcygeal area in young men, and occasionally can be found in other ectopic sites. We present a retrospective case review on unusual locations of pilonidal sinuses in the past 4 years. The lesion sites were as follows: one on the penis, two on the scalp, two on the abdomen, one on the neck, two in the groin and two in the axilla. Abdominal and penile lesions are uncommon, but the other locations reported are unusually rare. To our knowledge, the groin has not been re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 10 publications
0
29
0
Order By: Relevance
“…In an earlier series of HS patients, we found that 82% (49/60) showed multiple localizations; 18% (9/49 patients) of them suffered from lesions in the perianal/coccygeal region [33]. In these cases, the clinical diagnosis of HS was evident because other typical areas were involved; thus, consideration of PS or ‘atypical’ PS (as already reported earlier [22]) did not arise. Hence, PS could be regarded as a monolocalized form of HS.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…In an earlier series of HS patients, we found that 82% (49/60) showed multiple localizations; 18% (9/49 patients) of them suffered from lesions in the perianal/coccygeal region [33]. In these cases, the clinical diagnosis of HS was evident because other typical areas were involved; thus, consideration of PS or ‘atypical’ PS (as already reported earlier [22]) did not arise. Hence, PS could be regarded as a monolocalized form of HS.…”
Section: Discussionmentioning
confidence: 75%
“…(3) The presumed entity PS was also recognized in areas other than the sacrococcygeal region [21], especially in further regions with skin folds [10,22]. Hence, the idea arises that PS has considerable similarity or even identity to HS.…”
Section: Introductionmentioning
confidence: 99%
“…There are also no terminal hairs, but typical localizations (such as the intermammary folds in women) also lack terminal hairs, which do not seem to be an anatomical requisite of HS lesions. Atypical locations of pilonidal sinuses (a lesion frequently associated with HS) have been described, including lesions of the groin reminiscent of HS [15]. …”
Section: Discussionmentioning
confidence: 99%
“…Sion-Vardy et al mentioned in their study about that the related previously reported cases were non-hirsute healthy women, aged 17-30 years. However, our presented case in November 2009 is a hirsute 25-year-old woman [4].…”
Section: To the Editormentioning
confidence: 82%